(2E)-1-(6-Chloro-2-methyl-4-phenylquinolin-3-yl)-3-phenylprop-2-en-1-one - Tan, Kong Wai; Tiekink, E.R.T.; Viji, A.J.; Sarveswari, S.; Vijayakumar, V. (International Union of Crystallography, 2010)
In the title compound, C(25)H(18)ClNO, the conformation about the C=C double bond is E. Significant twists are evident in the molecule, with the benzene ring forming a dihedral angle of 53.92 (11)degrees with the quinolinyl residue. Further, the chalcone residue is approximately perpendicular to the quinolinyl residue [C(q)-C(q)-C(c)-O(c) torsion angle = -104.5 (3)degrees, where q = quinolinyl and c = chalcone]. In the crystal, the presence of C-H center dot center dot center dot O and C-H center dot center dot center dot pi interactions leads to supramolecular layers lying parallel to ((1) over bar 02).